A taxonomy for congestion control algorithms in packet switching networks. - Cui-Qing Yang (IEEE Network : the magazine of global information exchange)
The authors propose a new taxonomy for congestion control algorithms in packet switching computer networks based on control theory. They view a network as a large, distributed control system, in which a congestion control scheme is a (distributed) control policy executable at each node (host or switches) of the network in order to a certain level of stable conditions. This taxonomy provides a coherent framework for the comparative study of existing algorithms and offers clues toward the development of new congestion control strategies